Edukasi Multi Bahasa Dengan Metode Gamified Learning Berbasis ICT Untuk Murid Madrasah Ibtidaiyah Mabniyatul Ihsan Desa Balongwono Kecamatan Trowulan Kabupaten Mojokerto - Lailatus Sa'adah; Nia Aprilia; Dinda Fadhilah Novarinda; Firosa Faizati; Anissa Selvia Elsant; Mega Putri Wulandari; Syaidatul Mukaromah (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2026)
This Community Service Program (KKN) was conducted as a form of student contribution to the development of primary education, particularly at Madrasah Ibtidaiyah Mabniyatul Ihsan, located in Balongwono Village, Trowulan District, Mojokerto Regency. The program aimed on improving early childhood language literacy through a multilingual education approach, covering English and Arabic. To support the effectiveness of learning, the program employed a method of gamified learning based on Information and Communication Technology (ICT)—an approach that integrates game elements into the learning process using digital technology as the medium. The background of this program stemmed from the low interest in foreign language learning among students and the limited availability of interactive learning media in rural madrasahs. The implementation of the program showed positive results. The results are visible from the increase in the average foreign language ability of students from 68.5 to 80. Overall, this program not only provided students with a new and enjoyable learning experience but also strengthened the synergy between technology, education, and community empowerment. Multilingual education using ICT-based gamified learning has proven to be an effective approach to improving the quality of education in madrasahs and has the potential to be replicated in other regions with similar conditions.